David E. Schoonover, ed., with a foreword by Kenneth Cmiel: The Ladies’ Handbook - Jaine, Tom (Petits Propos Culinaires, 2024)
David E. Schoonover, ed., with a foreword by Kenneth Cmiel: The Ladies’ Handbook: University of Iowa Press, Iowa City, 2001: ISBN 0-87745-768-9: 80 pp., b/w illus., h/b, £21.50.